Los juegos de integracion y su influencia en el desarrollo cognitivo de los niños y niñas de tres a cuatro años en la escuela Lic. Jaime Andrade Fabara provincia de Cotopaxi cantón Latacunga parroquia Ignacio Flores en el año lectivo 2014-2015 - Taco Chicaiza, Janeth Alexandra (2016)
This Research Aims As Main Objective: To Develop A Working Guide About Integrating Games, Its Importance In The Learning And How Influential It Is On The Children´S Cognitive Development From three To four Years At Lic. Jaime Andrade Fabara School. This Was Developed With The Help Of Applied Research Instruments Such As: Interviews And Observation Forms To School Principal, Teachers, Parents And Children, It Could Be Determined So That, Children Have A Cognitive Development, It Is Necessary A Guide About Integrating Games. To Get The Information This Allowed Structuring The Proposal, Research Methods Were Used, Which Meant A Great Contribution To The Development Of Theoretical Framework Research Framework And The Proposal. As A Result On The Research Done, It Led To The Work Guide About Integrating Games Development And Its Importance In The Learning And How To Affect In The Children´S Cognitive Development From 3 To 4 Years At Lic. Jaime Andrade Fabara School, It Was Found That There Was No A Working Guide Of Integration Game At School.